Why Does Training Improve Revenue but Not Through Business Capacity? Evidence from Government-Sponsored Microenterprise Development Programs in Kabupaten Tanah Datar Regency - Siska Denny Zoebir; M. Nazer (Yayasan Riset dan Pengembangan Intelektual, 2026)
Training programs are widely used by local governments to improve the performance of microenterprises. Drawing upon Human Capital Theory and the Resource-Based View, this study examines the effect of training on revenue growth, with business capacity as a mediating variable among microenterprises in Tanah Datar Regency, Indonesia. The study employed a quantitative explanatory approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 56 microenterprise owners who participated in government-sponsored training programs organized by the Department of Cooperatives, Small and Medium Enterprises, and Trade of Tanah Datar Regency in 2023. To enrich the interpretation of the quantitative findings, follow-up interviews were conducted with selected participants. The results indicate that training has a positive and significant effect on business capacity and revenue growth. However, business capacity does not significantly affect revenue growth and therefore does not mediate the relationship between training and business performance. Follow-up interviews suggest that limited market access, weak business networks, and external economic conditions may constrain microenterprises from translating improved managerial practices into higher revenue. These findings imply that training alone is insufficient to generate sustainable business growth. Policy interventions should therefore be complemented by measures that facilitate market access, business partnerships, and post-training support. This study contributes to the microenterprise development literature by providing evidence that improvements in business capacity do not necessarily lead to improved business performance in local economic contexts.